2016
DOI: 10.1021/acs.chemrestox.5b00457
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Induces Migration through a GPER-, FAK-, Src-, and ERK2-Dependent Pathway in MDA-MB-231 Breast Cancer Cells

Abstract: Bisphenol A (BPA) is an industrial synthetic chemical utilized in the production of numerous products including food and beverage containers. Humans are exposed to BPA during ingestion of contaminated water and food because it can leach from polycarbonate containers, beverage cans, and epoxy resins. BPA has been related with the development of several diseases including breast cancer. However, the signal transduction pathways mediated by BPA and its role as a promoter of migration and invasion in breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…On the basis of these findings, we therefore focused on the gene expression profile and the signaling pathways associated with GPER in ER-negative BC patients. Of note, the expression of pro-metastatic CAMs, ECM-receptor interaction, and FA genes was found as the most correlated with GPER in this cell context, suggesting the potential of GPER to contribute to spreading and metastatic outgrowth of BC cells, as previously reported [7,19,[33][34][35][36]. CAMs are cell surface glycoproteins involved in the establishment of normal tissue structure and function, hence contributing to a variety of physiological processes as morphogenesis, embryogenesis, organogenesis, immunological function, wound healing, and inflammation [37].…”
Section: Discussionsupporting
confidence: 80%
“…On the basis of these findings, we therefore focused on the gene expression profile and the signaling pathways associated with GPER in ER-negative BC patients. Of note, the expression of pro-metastatic CAMs, ECM-receptor interaction, and FA genes was found as the most correlated with GPER in this cell context, suggesting the potential of GPER to contribute to spreading and metastatic outgrowth of BC cells, as previously reported [7,19,[33][34][35][36]. CAMs are cell surface glycoproteins involved in the establishment of normal tissue structure and function, hence contributing to a variety of physiological processes as morphogenesis, embryogenesis, organogenesis, immunological function, wound healing, and inflammation [37].…”
Section: Discussionsupporting
confidence: 80%
“…How BPA affects cell proliferation and, more widely, cell behavior through PKD1 phosphorylation remains an open question. As mentioned earlier, BPA was shown to regulate different signaling pathways such as ERK (Dong et al, 2011;Song et al, 2015), EGFR (Sauer et al, 2017), FAK, and Src (Castillo et al, 2016). BPA was also described to modulate the expression of both cellcycle related genes (Lee et al, 2012) and miRNA (Tilghman et al, 2012) in MCF-7 cells.…”
Section: ) [Review Inmentioning
confidence: 69%
“…In fact, aside from these genomic processes, BPA also acts via non-genomic and ER-independent mechanisms through the regulation of intracellular signaling pathways. In breast cancer cells, BPA has been shown to activate ERK (Dong et al, 2011;Song et al, 2015), EGFR (Sauer et al, 2017), FAK, and Src (Castillo et al, 2016), bind to small GTP binding proteins (Schopel et al, 2016), modulate the phosphatidylinositol 3-kinase (PI3-K)/Akt signaling pathway (Goodson et al, 2011), and down-regulate PTEN expression (Wang et al, 2014). These signaling pathways may be activated through binding of BPA to membrane receptors, such as GPR30 (Thomas and Dong, 2006;Dong et al, 2011) or through metalloprotease-mediated shedding of EGFR ligands, leading to EGFR activation (Sauer et al, 2017;Urriola-Munoz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By binding to GPER1, BPA induced activation of ERK1/2 and transcriptional regulation of c-fos in human breast cancer cells via the AP1-mediated pathway (Dong et al 2011). Additionally in breast cancer cells and through GPER1, BPA activated signal transduction pathways; it mediated migration and invasion by inducing the expression of kinases such as FAK, Src and ERK2 and by increasing AP-1 and NFκB-DNA binding activity through a Src-and ERK2-dependent pathway (Castillo Sanchez et al 2016). Interestingly, in non-hormonal cancers, BPA binds to GPER1 and induces cancer progression in laryngeal squamous cell carcinoma and lung cancer cells (Li et al 2017, Zhang et al 2014.…”
Section: Gper1 and Cancermentioning
confidence: 98%
“…Additionally, Andrysík et al (2013) demonstrated that the AhR agonist TCDD was able to disrupt contact inhibition and reduce gap junctional intercellular communication via downregulation of connexin-43 in an AhR-dependent manner. In addition, activation of B[a]P-dependent signal transduction pathway, where AhR involvement is primordial in B[a]P-induced carcinogenesis, also interferes with biological processes involved in migration and invasion of breast cancer cells and Triple Negative Breast Cancer (TNBC) cells which represents the worse prognosis sub-type in breast cancer (Castillo-Sanchez et al 2013, Shimizu et al 2000.…”
Section: Ahr and Cancermentioning
confidence: 99%